2005
DOI: 10.1111/j.1399-3046.2005.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus in pediatric patients: Results in the first 6 months post‐renal transplant

Abstract: We report our experience with sirolimus in children during the first 6 months after renal transplantation. From July 2000 to January 2004, 66 children received 33 deceased donor and 33 living donor transplants. Maintenance immunosuppression included sirolimus 3 mg/m(2) in addition to prednisone and tacrolimus or cyclosporine. Patient survival was 100% and graft survival was 65 of 66. Seven children experienced acute rejection episodes. All were reversible with increased doses of corticosteroid. One case of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 9 publications
1
43
1
Order By: Relevance
“…13,23 This observation is of concern for proposed trials in children with generalized arteriopathy because rapamycin can have serious side-effects in pediatric transplant recipients even at the dose used for immunosuppression. 24 Besides our study, somatic growth retardation by rapamycin has been observed in mouse embryos 16 and in young rats. 25 This phenomenon in children is controversial with one study finding adverse effects of rapamycin on growth of pediatric transplant recipients, 26 whereas another study found normal linear growth in a similar cohort.…”
Section: Discussionmentioning
confidence: 96%
“…13,23 This observation is of concern for proposed trials in children with generalized arteriopathy because rapamycin can have serious side-effects in pediatric transplant recipients even at the dose used for immunosuppression. 24 Besides our study, somatic growth retardation by rapamycin has been observed in mouse embryos 16 and in young rats. 25 This phenomenon in children is controversial with one study finding adverse effects of rapamycin on growth of pediatric transplant recipients, 26 whereas another study found normal linear growth in a similar cohort.…”
Section: Discussionmentioning
confidence: 96%
“…Previous unreported defective linear growth associated with SRL may be explained by the fact that only 3% of pediatric KTx recipients received SRL 1 month after the transplant and fewer afterwards [11]. SRL has been used for children at the early post-transplant phase [12], but many patients had to be switched to CNIs because of frequent side effects such as infection, pneumonitis, surgical wound healing problems or lymphoceles [13]. However, SRL is commonly used to replace CNIs in cases of steroidresistant acute rejection, malignancy, diabetes, neurotoxicity, or nephrotoxicity [4], and chronic allograft dysfunction is the main indication for SRL in children with transplants [2].…”
Section: Discussionmentioning
confidence: 99%
“…Use immediately posttransplant has been described in conjunction with a calcineurin inhibitor in a series of 66 pediatric renal transplant recipients, with effective immunosuppression but adverse effects necessitating drug withdrawal in 20% of patients [10]. The combination of interleukin (IL)-2 receptor antibody, sirolimus and mycophenolate, has been used occasionally [11][12][13] and, as it avoids the need for nephrotoxic drugs, there is potential for this combination to increase long-term graft survival.…”
Section: Introductionmentioning
confidence: 99%